1992
DOI: 10.1111/j.1471-4159.1992.tb10041.x
|View full text |Cite
|
Sign up to set email alerts
|

Excitatory Transmitter Amino Acid Release from the Ischemic Rat Cerebral Cortex: Effects of Adenosine Receptor Agonists and Antagonists

Abstract: The effects of selective adenosine receptor agonists [N6-cyclopentyladenosine (CPA) and N-ethylcarboxamidoadenosine (NECA)] and antagonists [8-cyclopentyl-1,3-dipropylxanthine (DPCPX) and 9-chloro-2-(2-furanyl)-5,6-dihydro-1,2,4-triazolo[1,5-c]quinazoline-5-im ine (CGS-15943A)] on aspartate and glutamate release from the ischemic rat cerebral cortex were studied with the cortical cup technique. Cerebral ischemia (for 20 min) was elicited by four-vessel occlusion. Excitatory amino acid releases were compared fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(60 citation statements)
references
References 40 publications
3
57
0
Order By: Relevance
“…This might suggest that activation of A2 receptors is able to suppress the effects of activating Al receptors. A similar inhibition by A2 (Simpson et al, 1992). It has also been invoked to explain the interactions of adenosine receptor agonists on catalepsy observed by Zarrindast et al (1993).…”
Section: Discussionmentioning
confidence: 85%
“…This might suggest that activation of A2 receptors is able to suppress the effects of activating Al receptors. A similar inhibition by A2 (Simpson et al, 1992). It has also been invoked to explain the interactions of adenosine receptor agonists on catalepsy observed by Zarrindast et al (1993).…”
Section: Discussionmentioning
confidence: 85%
“…It has already been shown that the mRNA encoding this receptor is transiently expressed in the developing cortex (Weaver, 1993) and that A2A receptor activation can regulate the release of GABA and glutamate from the ischaemic cortex Simpson et al, 1992). In addition the A2A receptor regulates neuronal excitability (Sebastiao et al, 1994) and acetylcholine release in the hippocampus (Cunha et al, 1994b).…”
Section: Discussionmentioning
confidence: 99%
“…Under these conditions, the concentration of adenosine available increases and activates A1Rs to reduce excitotoxicity (Fowler, 1989;Simpson et al, 1992;Katchman and Hershkowitz, 1993;Sweeney, 1997). A2 A Rs are often considered excitatory, potentiating the release of excitatory neurotransmitters .…”
Section: A2 a Rs Enhance Ipsps But Not Epspsmentioning
confidence: 99%